David Copperfield - Dickens, Charles, 1812-1870 (Oxford world's classics (Oxford University Press), 1999)
Ì have in my heart of hearts a favourite child. And his name is DAVID COPPERFIELD, ' wrote Dickens of what is the most personal, certainly one of the most popular, of all his novels. Dickens wrote the book after the completion of a fragment of autobiography recalling his employment as a child in a London warehouse, and in the first-person narrative, a new departure for him, realized marvellously the workings of memory. The embodiment of his boyhood experience in the novel involved a c̀omplicated interweaving of truth and fiction', at its most subtle in the portrait of his father as Mr Micawber.